VD_FINDINFO Jug / 2023 / 494 vom 11. Juli 2023 - VD Tribunal cantonal (2023)
FIXATION DE LA PEINE, EXPULSIONDROIT PÉNAL, APPRÉCIATION DES PREUVES, IN DUBIO PRO REO, CONSTATATION DES FAITS | 47 CP, 66b CP, 10 CPP (CH)